Psychometric Development of a Knowledge Test on Tick Infestation in Small Ruminants - Manju Sahu; Jayant Goyal; Ajay Kumar Chaturvedani; Souti Prasad Sarkhel; Sarvan Kumar; M.R. Vineeth; Rashmi Vishwakarma (Indian Journal of Extension Education, 2025)
A test was developed to assess farmers’ knowledge of tick infestation in small ruminants. Following the literature review, experts’ input, and pilot findings, a list of 48 items was identified and screened for relevancy by experts, resulting in 36 items retained for item analysis. These items were pretested during 2024-25 on 60 purposively selected farmers from non-sampling areas using a direct interview method with dichotomous scoring of ‘1’ for correct and ‘0’ for incorrect response. Based on item difficulty and discrimination indices, 30 items were finalized. Validity of the instrument was established using point-biserial correlation, with all items exhibiting acceptable correlation values of more than 0.30. Reliability of the tool was measured by the Kuder-Richardson Formula 20 and was found to be excellent with the value of 0.9162. Finally, the test consisted of 30 well-structured items organized under six thematic dimensions of tick infestation. The developed test offers a valuable means to assess farmers’ knowledge, serving as a foundation for developing targeted awareness and capacity-building interventions.